PENYULUHAN PENTINGNYA KERAGAMAN PANGAN KELUARGA DALAM PENCEGAHAN BALITA GIZI KURANG DI WILAYAH POSYANDU CEMPAKA, DESA SEKOLATON, KECAMATAN GONDANGREJO - Aryanti Setyaningsih; Bahriyatul Ma’rifah (Jurnal Abdimas Bina Bangsa, 2023)
Malnutrition problems in toddlers are often associated with a lack of ability and knowledge of mothers about parenting styles related to eating and a low variety of feeding. The purpose of this activity is that mothers have good knowledge and skills in choosing and providing a variety of foods for toddlers as an effort to prevent underweight toddlers in the Cempaka Posyandu area, Selokaton Village, Gondangrejo District. A total of 21 mothers out of 38 mothers of toddlers attended this activity (55.2%). Counseling and interactive discussion were chosen as the methods in this activity. Evaluation of activities is carried out using a pretest and posttest to determine changes in the mother's knowledge related to the material provided. Based on the results of the posttest, as much as 70.58% of mothers with toddlers had an increase in knowledge. It is hoped that an increase in mothers' knowledge related to parenting and the importance of food diversity, can increase the ability of mothers to provide food for their toddlers and prevent the occurrence of malnutrition problems in toddlers